Shallow Hal - Thomas, Bradley; Wessler, Charles B.; Farrelly, Bobby; Farrelly, Bobby; Farrelly, Bobby; Farrelly, Peter; Farrelly, Peter; Farrelly, Peter; Moynihan, Sean (20th Century Fox Home Entertainment, 2001)
Jack Black is Shallow Hal, a superficial skirt chaser who, after a mind-altering experience with a self-guru, doesn't realize that his gorgeous girlfriend (Gwyneth Paltrow) is actually a 300-pound not-so-hottie. Meanwhile, Hal's playboy pal Mauricio (Jason Alexander) is determined to break the spell before someone gets...squashed!